2013
DOI: 10.1080/13549839.2012.748723
|View full text |Cite
|
Sign up to set email alerts
|

Developing an “ecology of learning” within a school sustainability co-design project with children in New Zealand

Abstract: This paper analyses the inter-relatedness of layers of involvement, as contributing to learning, within a school sustainability project (the eco-classroom project). This engaged students, staff and community members (including professional practitioners) in an architectural co-design project that resulted, after 4 years, in a built classroom. The paper utilises an "ecology of learning" diagram to indicate layers and show connections, which are evidenced by findings from the project, alongside relevant literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…The dominance of the qualitative studies revealed that the researchers put emphasis on the process of developing and shaping students' competence, and stressed the interpretation of learning courses from the epistemic view [36]. The assumption of the qualitative evaluation was based on the interactive process of the researchers and those being researched in order to construct the understanding and meaning [32].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dominance of the qualitative studies revealed that the researchers put emphasis on the process of developing and shaping students' competence, and stressed the interpretation of learning courses from the epistemic view [36]. The assumption of the qualitative evaluation was based on the interactive process of the researchers and those being researched in order to construct the understanding and meaning [32].…”
Section: Methodsmentioning
confidence: 99%
“…The assumption of the qualitative evaluation was based on the interactive process of the researchers and those being researched in order to construct the understanding and meaning [32]. It also stressed the importance of learning conditions [10] for developing and qualifying action competence and focused on the learning process instead of overemphasizing the outcome of the project [36]. Action competence is not only characterized as holistic philosophy rooted in EE [10,16], but also corresponded to the emancipatory knowledge claim toward changing the status quo [35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication within families and family structure dominates the reverse socialization literature (Gentina & Singh, 2015) highlighting that children in contemporary families show an increasing level of personal agency/ownership around environmental sustainability (Kerrane, Hogg, & Bettany, 2012;Lawlor & Prothero, 2011;Wake & Eames, 2013). The children's environmental concern may act as a motivator to influence their parents (Easterling, Miller, & Weinberger, 1995).…”
Section: Environmental Educationmentioning
confidence: 99%
“…All six students who had attended one of the two primary schools indicated that one project had made a substantial impact, even drawing in members of the students' families. The project was to build an eco-classroom, and it inspired and encouraged student-directed planning, design and implementation (Wake & Eames, 2013). One of Craig's parents was involved and remembered this well:…”
Section: ) Significant Life Experiencesmentioning
confidence: 99%